Reflective Professional Practice in University Literary Education (Docentes 2.0 Journal, 2025)
Reflective professional practice in teaching university literature is an approach that goes beyond the simple transmission of knowledge, promoting a critical and collaborative dialogue between students and teachers, using a selection of literary texts as a basis. The aim was to foster a deep understanding and active analysis of literary texts, helping students improve their linguistic and writing skills and develop their emotional intelligence and creativity. The research used the hermeneutic method, constructivist paradigm, qualitative approach, and interpretive and cross-sectional grounded theory design. The population under study comprised 15 first-year students with a bachelor’s degree in English studies. Through reflective analysis and tools such as writing journals, students deepened their understanding of literary texts, recorded their emotions, and reflected on the impact of the text and their personal and cultural context. This process brought together the cognitive, the emotional, and the creative, improving literary appreciation and self-knowledge. Consequently, the practice contributed significantly to the comprehensive development of students, promoting a critical and conscious understanding of literary texts and a greater appreciation of the transformative power of literature in their lives, which aligns with meaningful learning.
Keywords: Reflective professional practice; understanding; creativity; literature